2021
DOI: 10.1007/s11356-021-13712-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of ionic and nanoparticulate zinc in the species Cymodoce truncata, Gammarus aequicauda and Paracentrotus lividus

Abstract: Due to the continuous development, production and consumption of nanoparticles (NPs), their release, fate and effects in marine coastal environment can represent a major concern. The aim of this study was to evaluate the toxicity of ZnO nanoparticles (ZnO NPs) and compare it to bulk ZnSO4 on three macroinvertebrates: the isopod Cymodoce truncata (i.e. used for the first time in ecotoxicology), the amphipod Gammarus aequicauda and the sea urchin Paracentrotus lividus. This study showed concentration- and time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…to ZnO induced severe and fast coral bleaching due to the alteration of the symbiosis between coral and zooxanthellae, while two modified forms of TiO 2 (Eusolex ® T2000 (Merck KGaA, Darmstadt, Germany) and Opti-sol™ (Oxonica Ltd. and UK Nanotechnology Company, Aylesbury, UK)) barely had any detrimental effects on corals, implying better eco-compatibility [122]. ZnO nanoparticles (nZnO) showed toxicity in macroinvertebrates: the isopod Cymodoce truncate, the amphipod Gammarus aequicauda and the sea urchin Paracentrotus lividus [123]; two marine crustaceans: copepod Tigriopus fulvus and the amphypod Corophium insidiosum [124]; and the crustacean Daphnia magna and zebrafish (Danio rerio) [125]. Similar effects have been observed with nTiO 2 inducing oxidative damage and genotoxic effects in the marine mussel Mytilus trossulus [126].…”
Section: Coral Reefsmentioning
confidence: 99%
“…to ZnO induced severe and fast coral bleaching due to the alteration of the symbiosis between coral and zooxanthellae, while two modified forms of TiO 2 (Eusolex ® T2000 (Merck KGaA, Darmstadt, Germany) and Opti-sol™ (Oxonica Ltd. and UK Nanotechnology Company, Aylesbury, UK)) barely had any detrimental effects on corals, implying better eco-compatibility [122]. ZnO nanoparticles (nZnO) showed toxicity in macroinvertebrates: the isopod Cymodoce truncate, the amphipod Gammarus aequicauda and the sea urchin Paracentrotus lividus [123]; two marine crustaceans: copepod Tigriopus fulvus and the amphypod Corophium insidiosum [124]; and the crustacean Daphnia magna and zebrafish (Danio rerio) [125]. Similar effects have been observed with nTiO 2 inducing oxidative damage and genotoxic effects in the marine mussel Mytilus trossulus [126].…”
Section: Coral Reefsmentioning
confidence: 99%
“…In the literature, there are sufficiently convincing data demonstrating the effect of ZnO NPs on various functional aspects of marine organisms [ 20 , 21 , 22 ]. A number of studies have revealed a higher toxicity of ZnO NPs, not only in relation to those that are identical in size to particles of oxides of other metals [ 23 , 24 ], but also in comparison with zinc ions [ 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the ocean is the ultimate sink for NPs (Klaine et al, 2008), concerns are increasing about the possible risks posed by NPs to marine environments and especially to marine organisms. An increasing number of studies have reported that the metallic NPs caused significant toxicity to marine organisms, including marine bacteria (Rotini et al, 2017;Schiavo et al, 2018), algae (Xia et al, 2015;Fazelian et al, 2019;Thiagarajan et al, 2019), copepods (Rotini et al, 2018;Farkas et al, 2020), crustaceans (Rotini et al, 2018;Prato et al, 2021), echinoderms (Rotini et al, 2018;Prato et al, 2021), and mollusks (Libralato et al, 2013;Zha et al, 2019;Zha et al, 2022), with a 50% lethal/effect concentration (LC 50 /EC 50 ) varied widely from 0.001-116.981 mg/L.…”
Section: Introductionmentioning
confidence: 99%